FORAMINIFERA BENTIK PADA PADANG LAMUN DI KAWASAN PANTAI SEKITAR PULAU BUNAKEN SULAWESI UTARA - Feby GB Kombo; Jane M Mamuaja; Royke M Rampengan; Billy Th Wagey; Calvyn FA Sondakh; Henneke Pangkey (Sam Ratulangi University, 2019)
Benthic foraminifera lives on the seaflor and some of them are attached to plant stem. This organisms use pseudopodia to move. The study aims to describe the groups of foraminifera that live on leaves and seagrass sediments and provide information on the comparison of the number of benthic foraminifera genera in seagrass beds. The study was performed in Bunaken Island and during the study a number of 4593 specimens of benthic foraminifera has been identified and they are divided into specimen that lives on seagrass leaves (1097 specimens) and specimens that live on sediments (3496 specimens). The specimen was grouped in 16 genera and they were scattered in 2 stations within four sampling points. These genera are: Amphistegina, Calcarina, Coscinospira, Elphidium, Eponides, Lachlanela, Marginophora, Neorotalia, Operculina, Cleroplis, Planorbulina, Pseudorotalia, Quinqueloculina, Sorites, Spiroluculina, and Triloculina. Benthic foraminifera in seagrass leaves consist of 16 genera which are characterized by the genus Marginophora and Amphistegina and those live in substratum consist of 14 genera which was characterized by the genus Amphistegina.Keywords : Benthic Foraminifera, Seagrass beds, Bunaken Island